PROTESTANTISM – REGULATION OF CONSUMPTION - Vladimir A. Ermolaev (Russian Studies in Culture and Society)
In the article, the author examines the gastronomic culture and its regulatory function, expressed in the regulation of eating behavior and food consumption by people through the existence of prohibitions and permits. In particular, it is indicated that such tools, as a rule, find their place in religious canons (codes of rules).